The Implementation of Scratch Learning Media to Improve Students’ Learning Outcomes and Learning Activities in the Fiqh Subject for Grade V at Mi Al-Ma’arif Sidolaju Ngawi - Darda, Abu; Ikmah, Amit Dana; Hasanah, Faridatul; Islam, Muhammad Thoriqul (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to improve student learning outcomes and engagement through the use of technology-based introductory learning media in the Fiqh subject at MI Al-Ma’arif Sidolaju Ngawi. The problem underlying this study is the low level of student participation and learning outcomes that have not yet met the Minimum Passing Criteria (KKM), caused by the dominance of traditional teaching methods and the limited use of learning media appropriate to the students’ characteristics. This study employs a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted over two cycles. The research subjects consisted of 22 Year 5 pupils in the 2024/2025 academic year. Data collection techniques included observation of pupil activities, learning outcome tests, interviews, and documentation. Each cycle comprised the planning, implementation, observation, and reflection stages. The results of the study showed an increase in student learning activity from 51.6% in cycle I to 57.92% in cycle II. Furthermore, the average learning outcome score increased from 63 in cycle I to 80 in cycle II. These findings indicate that the use of technology-based introductory learning media is effective in enhancing student engagement and learning outcomes in the subject of Fiqh. This study is limited by a small sample size, the scope of a single class, and a relatively short research duration, so the results cannot yet be generalized widely. Therefore, future research is recommended to involve larger samples, more diverse contexts, and longer implementation periods to obtain more comprehensive findings.